2008
DOI: 10.1098/rsbl.2008.0253
|View full text |Cite
|
Sign up to set email alerts
|

The sweet life: diet sugar concentration influences paracellular glucose absorption

Abstract: Small birds and bats face strong selection pressure to digest food rapidly in order to reduce digesta mass carried during flight. One mechanism is rapid absorption of a high proportion of glucose via the paracellular pathway (transfer between epithelial cells, not mediated by transporter proteins). Intestinal paracellular permeability to glucose was assessed for two nectarivorous passerines, the Australian New Holland honeyeater (Phylidonyris novaehollandiae) and African white-bellied sunbird (Cinnyris talatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Silvereyes and singing honeyeaters showed greater bioavailability of both l-glucose and d-xylose on the more concentrated diet, where slower gut passage time would promote increased absorption via the paracellular route (likely because of increased contact time of digesta with absorptive surfaces), as has been previously described in three specialized nectarivores to date (McWhorter et al 2006;Napier et al 2008b). On the other hand, mistletoebirds did not vary f with diet concentration for either sugar.…”
Section: Mechanism Of Sugar Absorptionmentioning
confidence: 65%
See 3 more Smart Citations
“…Silvereyes and singing honeyeaters showed greater bioavailability of both l-glucose and d-xylose on the more concentrated diet, where slower gut passage time would promote increased absorption via the paracellular route (likely because of increased contact time of digesta with absorptive surfaces), as has been previously described in three specialized nectarivores to date (McWhorter et al 2006;Napier et al 2008b). On the other hand, mistletoebirds did not vary f with diet concentration for either sugar.…”
Section: Mechanism Of Sugar Absorptionmentioning
confidence: 65%
“…Paracellular absorption provides a nonsaturable absorptive mechanism that matches absorption capacity to acute changes in dietary nutrient concentration (Afik et al 1997;Ferraris 2001). The relative contribution of paracellular to total glucose absorption in nectarivorous birds increases with an increase in diet sugar concentration, an effect that may be largely due to increased digesta retention time of more energy-dense nectars in the intestine (McWhorter et al 2006;Napier et al 2008b). Frugivorous birds and bats also rely extensively on the paracellular pathway for the absorption of glucose McWhorter et al 2010), but the effects of diet energy density and thus digesta transit or residence times have not been assessed in frugivorous species to date.…”
Section: Mistletoebirds and Xylose: Australian Frugivores Differ In Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Paracellular transport of glucose appears to account for a relatively small proportion of total glucose uptake (∼5%) in nonflying mammals such as rats (O'Rourke et al 1995;Uhing and Kimura 1995), dogs (Lane et al 1999;Pencek et al 2002Pencek et al , 2003, and humans (Fine et al 1993). Recent studies using uniform methodology have shown convincingly, however, that small birds (Karasov and Cork 1994;Levey and Cipollini 1996;Afik et al 1997;Chediack et al 2001Chediack et al , 2003Napier et al 2008b) and bats CaviedesVidal et al 2008) rely extensively on nonmediated mechanisms of absorption. In these animals, paracellular nutrient uptake supplements carrier-mediated absorption, allowing them to maintain high digestive efficiency in spite of generally smaller intestines, lower absorptive surface area, and relatively rapid digesta throughput (Caviedes-Vidal et al 2007).…”
Section: Introductionmentioning
confidence: 99%